2020
DOI: 10.3389/fnins.2020.00085
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Compound Heterozygous Mutations in the GAN Gene of a Chinese Patient Diagnosed With Giant Axonal Neuropathy

Abstract: Giant axonal neuropathy (GAN) is a very rare autosomal recessive disorder characterized by abnormally large and dysfunctional neuronal axons. Mutations in the GAN gene have been identified as the cause of this disorder. In this report, we performed a detailed phenotypic assessment of a Chinese patient with GAN. An array-based exon capture test and targeted next-generation sequencing were used to detect the suspected mutation sites. Compound heterozygous mutations of p.S79L (c.236C > T) in the BTB domain and p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…This has been also suggested based on studies that analyzed the features of 75 children with peripheral inherited neuropathies [ 13 ]. For that, it is widely recommended to use the aid of neuropathology findings in nerve biopsy as well as laboratory evaluation and other neuroradiological modalities to evaluate, monitor, and follow up with cases carrying this variant [ 14 , 15 ]. As such, this was the adopted approach in our case that yielded successful early detection of the variant and subsequently proper follow-up plans.…”
Section: Discussionmentioning
confidence: 99%
“…This has been also suggested based on studies that analyzed the features of 75 children with peripheral inherited neuropathies [ 13 ]. For that, it is widely recommended to use the aid of neuropathology findings in nerve biopsy as well as laboratory evaluation and other neuroradiological modalities to evaluate, monitor, and follow up with cases carrying this variant [ 14 , 15 ]. As such, this was the adopted approach in our case that yielded successful early detection of the variant and subsequently proper follow-up plans.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of MAP1B and TBCB proteins can disrupt the movement of motor proteins and may affect transport processes by altering microtubule dynamics, which leads to morphological and functional changes in the neurofilament network, distension and demyelination of axonal fibers, cell death, and subsequently neurodegenerative disorders such as giant axonal neuropathy (Allen et al, 2005 ; Bomont et al, 2000 ; Wang et al, 2005 ; Xu et al, 2020 ). Allen et al showed that gigaxonin recruits ubiquitin‐activating enzyme E1 (UBA1) via its BTB domain and controls the degradation of MAP1B and TBCB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neuropathology finding in nerve biopsy, such as giant axons, is not only specific to GAN but also considered an invasive method (Jaffer et al, 2012 ). Laboratory evaluation results are also nonspecific and neuroimaging findings comprise heterogeneous and nonspecific features, that could not lead to narrowing the differential diagnosis (Aharoni et al, 2016 ; Almeida et al, 2016 ; Cai et al, 2018 ; Echaniz‐Laguna et al, 2020 ; Edem et al, 2019 ; Garg et al, 2018 ; Jain et al, 2014 ; Johnson‐Kerner et al, 2014 ; Kamate et al, 2014 ; Koichihara et al, 2016 ; Mohammad et al, 2014 ; Xu et al, 2020 ). As a result, molecular diagnostic methods, such as whole‐exome sequencing, play a key role in approaching these patients (Bacquet et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, gigaxonin plays an important role in the breakdown of neurofilament (NF) [ 8 ], where the cellular hallmark of GAN pathology is the formation of its large aggregates [ 2 , 3 , 5 ]. According to the Leiden Open Variation Database (LOVD) (updated 2022), National Center for Biotechnology Information (NCBI) (updated 2022), and the mutation summary reported by Lescouzères and Bomont, P. (2020), there are 89 variants that lead to manifestation of GAN ( Figure 1 ) [ 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%